ATF6 is required for efficient rhodopsin clearance and retinal homeostasis in the P23H rho retinitis pigmentosa mouse model - Lee, Eun-Jin; Chan, Priscilla; Chea, Leon; Kim, Kyle; Kaufman, Randal J.; Lin, Jonathan H. (Scientific reports, 2021)
Retinitis Pigmentosa (RP) is a blinding disease that arises from loss of rods and subsequently cones. The P23H rhodopsin knock-in (P23H-KI) mouse develops retinal degeneration that mirrors RP phenotype in patients carrying the orthologous variant. Previously, we found that the P23H rhodopsin protein was degraded in P23H-KI retinas, and the Unfolded Protein Response (UPR) promoted P23H rhodopsin degradation in heterologous cells in vitro. Here, we investigated the role of a UPR regulator gene, activating transcription factor 6 ( Atf6 ), in rhodopsin protein homeostasis in heterozygous P23H rhodopsin ( Rho + /P23H ) mice. Significantly increased rhodopsin protein levels were found in Atf6 −/− Rho + /P23H retinas compared to Atf6 + /− Rho + /P23H retinas at early ages (~ P12), while rhodopsin mRNA levels were not different. The IRE1 pathway of the UPR was hyper-activated in young Atf6 −/− Rho + /P23H retinas, and photoreceptor layer thickness was unchanged at this early age in Rho + /P23H mice lacking Atf6 . By contrast, older Atf6 −/− Rho + /P23H mice developed significantly increased retinal degeneration in comparison to Atf6 + /− Rho + /P23H mice in all retinal layers, accompanied by reduced rhodopsin protein levels. Our findings demonstrate that Atf6 is required for efficient clearance of rhodopsin protein in rod photoreceptors expressing P23H rhodopsin, and that loss of Atf6 ultimately accelerates retinal degeneration in P23H-KI mice.